Prevalence of Gastrointestinal Helminths of Dogs and Associated Factors in Hawassa City of Sidama Region, Ethiopia - Teshager Dubie; Shilmat Sire; Gizachew Fentahun; Fanuel Bizuayehu (Journal of Parasitology Research)
A cross-sectional study was carried out in the Sidama region’s Hawassa town from March 2021 to July 2021 with the aim of estimating the prevalence and associated factors of dog gastrointestinal helminths. A total of 384 dogs were randomly selected, and their feces were examined using a flotation technique. For data analysis, descriptive statistics and chi-square analyses were employed, and a P-value of less than 0.05 was considered as significant. Accordingly, 56% (n=215; 95% CI, 49.26–62.66) of dogs had gastrointestinal helminth parasite infection, of which 42.2% (n=162) had a single infection and 13.8% (n=53) had a mixed infection. In this study, Strongyloides sp. was the most detected helminth (24.2%), followed by Ancylostoma sp. (15.37%), Trichuris vulpis (14.6%), Toxocara canis (5.73%), Echinococcus sp. (5.47%), and Dipylidium caninum (4.43%). Out of the total sampled dogs tested positive for one or more gastrointestinal helminths, 37.5% (n=144) were males and 18.5% (n=71) were females. The total prevalence of helminth infections did not change significantly (P>0.05) by the gender, age, and breed of dogs. The present study’s high prevalence of dog helminthiasis reflects a high occurrence of infection and a concern to the public’s health. In light of this conclusion, it is advised that dog owners improve their standards of hygiene. In addition, they should regularly take their animals to veterinary care and frequently administer the appropriate anthelmintics available to their dogs.